1995
DOI: 10.1111/j.1476-5381.1995.tb13325.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparisons of muscarinic and bradykinin receptor‐mediated Ins (1,4,5)P3 accumulation and Ca2+ signalling in human neuroblastoma cells

Abstract: Road, Leicester LEI 9HN 1 Muscarinic and bradykinin receptor-mediated Ins(1,4,5)P3 accumulation, Ca2+ mobilization and Ca2+ entry have been examined in human SH-SY5Y neuroblastoma cells. This has allowed both direct comparison of signalling events by two receptor types potentially linked to the same transduction pathway and an investigation of the interactions between the components of this pathway. 2 Stimulation of muscarinic receptors with carbachol produced biphasic accumulations of Ins(1,4,5)P3 consisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 38 publications
9
67
0
Order By: Relevance
“…7b). This sustained phase of [Ca 2ϩ ] i elevation is dependent upon the influx of extracellular Ca 2ϩ via an as yet undefined mechanism but which most likely involves capacita- tive entry (20). Addition of 1 M thapsigargin to these cells also resulted in capacitative Ca 2ϩ entry and a sustained elevation of [Ca 2ϩ ] i of similar magnitude to that mediated by 1 mM carbachol, but this was unaffected by 10 M wortmannin (data not shown).…”
Section: Effects Of Wortmannin and Ly-294002 On Basal And Agonist-stimentioning
confidence: 73%
See 2 more Smart Citations
“…7b). This sustained phase of [Ca 2ϩ ] i elevation is dependent upon the influx of extracellular Ca 2ϩ via an as yet undefined mechanism but which most likely involves capacita- tive entry (20). Addition of 1 M thapsigargin to these cells also resulted in capacitative Ca 2ϩ entry and a sustained elevation of [Ca 2ϩ ] i of similar magnitude to that mediated by 1 mM carbachol, but this was unaffected by 10 M wortmannin (data not shown).…”
Section: Effects Of Wortmannin and Ly-294002 On Basal And Agonist-stimentioning
confidence: 73%
“…Materials-Reagents of analytical grade were obtained from suppliers listed previously (20,21,24 3 H]phosphoinositides and PtdIns(4,5)P 2 mass, duplicates were pooled at the lipid extraction stage. All data are presented as mean Ϯ S.E.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies, particularly those in neuronal preparations, have demonstrated that agonist-stimulated PIC activation is facilitated by increases in [Ca2+], (Eberhard & Holz, 1988;del Rio et al, 1994;Wojcikiewicz et al, 1994;Willars & Nahorski, 1995). Facilitation of agoniststimulated PIC activity may be caused by Ca2" mobilization from intracellular stores or Ca2+-entry via a multitude of influx pathways (Simpson et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Inspection of Fig. 3 reveals that at the 12-min time point, a 100% recovery of functional response is elicited by only '--.50% of the original surface receptor number, indicative of a substantial receptor reserve for mobilization of intracellular Ca2~ (Willars and Nahorski, 1995).…”
Section: Role Of Receptor Internalization and Recycling In Resensitizmentioning
confidence: 99%